EFEKTIVITAS PENGGUNAAN APLIKASI KLINIK ASPIRASI DAN LAYANAN PENGADUAN (KINALANG) PADA ERA NEW NORMAL DI KOTA KOTAMOBAGU - MOKOGINTA, RALDY; POSUMAH, JOHNNY; PALAR, NOVIE (JURNAL ADMINISTRASI PUBLIK, 2021)
Effectiveness is the main element to achieve the goals or targets that have been determined in eachorganization, activity or program. The Aspiration Clinic and Complaints Service Application (Kinalang) is anapplication initiated by the Kotamobagu City Communication and Information Office (Diskominfo). Thisapplication was officially launched on Friday 6 December 2019 as a result of the development of the previousapplication program, namely the Public Complaints System (Sikemas). The New Normal order during thepandemic is changing behavior to continue to carry out normal activities, but coupled with implementing healthprotocols. The goal is to prevent the transmission of the corona virus, which continues to record additionalcases every day. This study looks at the effectiveness of using the Aspiration Clinic and Complaints Serviceapplication in the New Normal era in Kotamobagu. The author can examine the existence of kinalangformation in facilitating public aspirations and complaints and improving the quality of public services. Bothhave been realized and run well by the Department of Communication and Information of Kotamobagu City.This study uses a qualitative research method with a research focus taken from Duncan in Steers who divides3 dimensions in measuring effectiveness, namely Goal Achievement, Integration and Adaptation at theKotamobagu City Communication and Information Office.Keywords: Effectiveness, aplication, goal Approach, Integration, Adpatation